DISTANT IDENTITIES: THE CANARY ISLANDS NATIONALISTIC PROJECT IN AMERICA (1895-1933) (Tzintzun, Revista de Estudios Históricos, 2016)
The proposal of this work is the study of the Canary Islands nationalistic project inAmerica during the period of 1895-1933. There are two key moments in the historyof Canary Islands nationalism in America. The first of these took place in Caracas,coinciding with the Cuban War of Independence, while the second came about inHavana when Spain was under the dictatorship of Primo de Rivera. The twoattempts at construction of a Canary Islands nationalistic project in America alsocoincided with two crucial moments in Spanish and world history. These were theredistribution of colonial power with its loss of Cuba, Puerto Rico and the Philippines,and in the Spanish assumption of a brief protagonist attitude in North Africa.
Keywords: Canary islands nationalism project; Canary Islands identity; El Guanche; Canary Islands; José Martí; Cuba